Acute effect of multipoint pacing and fused AV delay in patients receiving cardiac resynchronization therapy - Masakazu Miyamoto; Nobuhiro Nishii; Tomofumi Mizuno; Akira Ueoka; Takuro Masuda; Saori Asada; Kentaro Ejiri; Satoshi Kawada; Koji Nakagawa; Kazufumi Nakamura; Hiroshi Morita; Shinsuke Yuasa (Journal of Arrhythmia)
Abstract Background Cardiac resynchronization therapy (CRT) is an established treatment for patients with heart failure with dyssynchrony. However, one‐third of patients do not respond positively to it. Recently, multipoint pacing (MPP), which involves pacing from two sites on the left ventricle, has been found to improve symptoms and hemodynamics compared to conventional CRT. An automatic fused atrioventricular (AV) delay that performs fused pacing for intrinsic conduction has also been introduced. However, the combined effect of MPP and fused AV delay on acute hemodynamics is unknown. Objective To evaluate the acute hemodynamic effects of MPP and fused AV delay in patients undergoing CRT. Methods A pressure wire was delivered to the left ventricle, and dp/dt was compared with single atrial stimulation pacing in 52 patients with various pacing configurations. Results Delta dp/dt was greater in MPP than in conventional CRT (10.5 ± 1.0% vs. 8.2 ± 1.0%, p < 0.001) and in fused AV delay than in short AV delay (10.4 ± 0.8% vs. 8.3 ± 1.1, p < 0.001). Hemodynamic parameters significantly most improved with the combination of MPP and fused AV delay. Delta dp/dt was greater in LV pacing than in biventricular (BiV) pacing with MPP and fused AV delay; however, the delta QRS duration was shorter in LV pacing than in BiV pacing. Delta dp/dt and delta QRS duration were negatively correlated. The super‐responder rate was 66%. Conclusion Combining MPP and fused AV delay has an additional effect. Shortening the QRS duration can increase the dp/dt, but the estimated line differs between LV and BiV pacing.